Peer pressure or personal choice? How peer working hours shape individual working hours preferences - Zarah Westrich (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2025)
Standard economic models view labour supply decisions as individual utility maximisation balancing the trade-off between income and leisure. In contrast, we focus on the social context as a central determinant and analyse how colleagues' working hours shape individual working hours preferences. Our analysis is based on a representative survey of employees in Germany that we conducted in October 2024 (N = 4,450). Combining novel survey experiment with a quantitative text analysis of an open-ended survey question enables us to identify a causal mechanism and to provide contextual insights into the role of social context for the formation of working hours preferences. We show that colleagues' working hours causally affect working hours preferences. The reasons given by the respondents for choosing the stated working hours, by contrast, are primarily personal. This shows that preferences are socially determined, even if they are rationalised in individualistic terms. Our findings emphasise the importance of collective action for working time policy and highlight methodological challenges that need to be considered when analysing and interpreting working time preferences.
Keywords: B55; D9; J22; 330; working hours; social comparisons; preference formation